Fuzzy Based Adaptive Controller for on - Chip Communication - Jasmin, M; Vigneswaran, T (International Journal of Engineering and Technology, 2018)
Occurrence of bit error is more when communication takes place in System on chip environment. By employing proper error detection and correction codes the bit error rate can be considerably reduced in On-chip communication. As System on chip involves heterogeneous system the efficiency of communication is improved when reconfigurable multiple coding schemes are preferred. Depending upon the requirements for various subsystem the correct code has to be selected. Due to the variations in input demands based on various subsystems the proper selection of codes become fuzzy in nature. In this paper Fuzzy Controller is designed to select the correct coding scheme. Inputs are given to the fuzzy controller based on the application demand of the user. The input parameters are minimum bit error rate, computational complexity and correlation level of the input data. Fuzzy Controller employs three membership functions and 27 rules to select the appropriate coding scheme. The selected coding scheme should be communicated at the proper time to the decoder. To enable the decoding process selected coding scheme is communicated effectively by using less overhead frame format. To verify the functionality of fuzzy controller random input data sets are used for testing.Â Â